2019
DOI: 10.24998/maeusabed.539891
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of curcumin on the blood tissue in rats

Abstract: Curcumin is a pigment found in Indian saffron spices, also known as turmeric. The aim of this study is to investigate the antioxidant effect of curcumin, a phytochemical, on the blood tissue of rats. In the study, 24 Wistar rats were 8 weeks old, randomly divided into 2 groups which were the control group and the experimental group was fed with curcumin supplement. Curcumin supplemented group was fed at 300mg/kg/day curcumin dissolved in corn oil by oral gavage for 12 days. 24 hours after the last feeding, TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Curcuma longa (zerdeçal) rizomlarında bulunan doğal bir polifenol olan kurkuminin, antienflamatuvar, antioksidan ve kemopreventif aktivite gösterdiği belirlenmiştir [90][91][92][93]. Hint safranı olarak da bilinen zerdeçala rengini veren majör biyoaktif bileşiklerin en önemlisi olan kurkumin, sulu çözeltide çözünmeyen hidrofobik bir bileşiktir.…”
Section: Eksozomlarin Bi̇yoakti̇f Bi̇leşi̇kleri̇n Taşinmasindaki̇ Rolleri̇unclassified
“…Curcuma longa (zerdeçal) rizomlarında bulunan doğal bir polifenol olan kurkuminin, antienflamatuvar, antioksidan ve kemopreventif aktivite gösterdiği belirlenmiştir [90][91][92][93]. Hint safranı olarak da bilinen zerdeçala rengini veren majör biyoaktif bileşiklerin en önemlisi olan kurkumin, sulu çözeltide çözünmeyen hidrofobik bir bileşiktir.…”
Section: Eksozomlarin Bi̇yoakti̇f Bi̇leşi̇kleri̇n Taşinmasindaki̇ Rolleri̇unclassified
“…Turmeric, derived from the roots of this plant, has been used in India for centuries as a spice, medical drug and cosmetic product. This plant, commonly used as a coloring agent in foods and contains tetrahydrocurcumin which is odorless and heat resistant antioxidant compound (Aggarwal et al, 2007). Curcumin is known has lots of pharmacological properties include anticancer, antiinflamatory, antioxidant and antiapoptotic effects (Kunnumakkara et al, 2008, Lin et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that due to its antioxidant properties, it prevents damage caused by exposure to harmful agents such as alcohol, drugs, radiation and heavy metals (Phillips et al, 2013). Especially, it is a plant used for the preservation and sweetening of foodstuffs (Aggarwal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%